2020
DOI: 10.1016/j.jphotobiol.2020.112017
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of aminolevulinic acid-mediated protoporphyrin IX fluorescence and enhancement by ABCG2 inhibitors in renal cell carcinoma cells

Abstract: Aminolevulinic acid (ALA) has been approved as an intraoperative molecular imaging probe for protoporphyrin IX (PpIX) fluorescence-guided resection of glioma. Here we explored its potential application for renal cell carcinoma (RCC) that is showing increased incidence in recent years. ALA-mediated PpIX in cell lysates (intracellular) and culture medium was measured in five human RCC cell lines (786-O, 769-P, A-704, Caki-1, Caki-2) and a non-tumor human kidney epithelial cell line HK-2 by spectrofluorometry and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 36 publications
3
12
0
Order By: Relevance
“…Effects of small molecule kinase inhibitors on ALA-PpIX fluorescence and PDT response were evaluated in TNBC cell lines in this study. The results confirmed our previous findings in renal cell carcinoma cell lines 9 and demonstrate in TNBC cell lines that clinically approved kinase inhibitors, such as lapatinib, sunitinib, and gefitinib, increased ALA-PpIX fluorescence. As in the previous study, we found here that lapatinib was the only kinase inhibitor that significantly increased intracellular PpIX and reduced PpIX efflux.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Effects of small molecule kinase inhibitors on ALA-PpIX fluorescence and PDT response were evaluated in TNBC cell lines in this study. The results confirmed our previous findings in renal cell carcinoma cell lines 9 and demonstrate in TNBC cell lines that clinically approved kinase inhibitors, such as lapatinib, sunitinib, and gefitinib, increased ALA-PpIX fluorescence. As in the previous study, we found here that lapatinib was the only kinase inhibitor that significantly increased intracellular PpIX and reduced PpIX efflux.…”
Section: Discussionsupporting
confidence: 91%
“…Our previous evaluation of over 12 kinase inhibitors led to the identification of lapatinib as the most potent drug for enhancing ALA-PpIX fluorescence. 9 This study further demonstrates the effectiveness of lapatinib in enhancing ALA-PDT by inducing apoptosis. Strong enhancement of ALA-PpIX fluorescence and PDT by lapatinib was likely due to its potent inhibition of ABCG2 activity.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations